The Gut Microbiome in Anorexia Nervosa: Friend or Foe? - Ghenciulescu, Ana; Park, Rebecca J.; Burnet, Philip W. J. (Frontiers in Psychiatry, 2021)
The human gut microbiome is emerging as a key modulator of homeostasis, with far-reaching implications for various multifactorial diseases, including anorexia nervosa (AN). Despite significant morbidity and mortality, the underlying mechanisms of this eating disorder are poorly understood, but the classical view defining AN as a purely psychiatric condition is increasingly being challenged. Accumulating evidence from comparative studies of AN and healthy faecal microbial composition reveals considerable low divergence and altered taxonomic abundance of the AN gut microbiome. When integrated with preclinical data, these findings point to a significant role of the gut microbiome in AN pathophysiology, via effects on host energy metabolism, intestinal permeability, immune function, appetite and behaviour. While complex causal relationships between genetic risk factors, dietary patterns and microbiome, and their relevance for AN onset and perpetuation have not been fully elucidated, preliminary clinical studies support the use of microbiome-based interventions such as faecal microbiota transplants and probiotics as adjuvants to standard AN therapies. Future research should aim to move from observational to mechanistic, as dissecting how specific microbial taxa interact with the host to impact the development of AN could help design novel therapeutic approaches that more effectively address the severe comorbidities and high relapse rate of this serious disorder.